СЕЙФУЛҒАБИТ МАЖИТОВТЫҢ ЖӘДИДШИЛИК-АҒАРТЫЎШЫЛЫҚ ХЫЗМЕТЛЕРИ - Сейтмуратов, Қ. (FAN va JAMIYAT, 2025)
The article talks about the educational – jadid activities and pedagogical views of Seyfulgabid Majidov, a famous poet-educator.